Polymer Pressure‐Sensitive Adhesive with A Temperature‐Insensitive Loss Factor Operating Under Water and Oil - Wang, Yan‐Jie; He, Yang; Zheng, Si Yu; Xu, Ziyang; Li, Jia; Zhao, Yiping; Chen, Li; Liu, Wenguang (Advanced functional materials, 2021)
Loss factor tan δ determines the viscoelasticity of a material. Higher or lower loss factor tanδ (>1 or <1) suggests a viscous or elastic material. Most polymer pressure‐sensitive adhesives (PSAs) possess a limited operational temperature range (near room temperature), above which the PSAs trend to be more viscous (un‐crosslinked) or more elastic (crosslinked), and below which PSAs become more elastic. These properties are unfavorable for PSA operation. Herein, an underwater PSA possessing short hydrophobic side chains and weak hydrogen bond interactions are described. Proper modulus and stable loss factor close to 1 contributes to an efficient adhesion underwater over a temperature range of 0–100 °C. Moreover, by introducing Teflon particles, the adhesion can be operated under silicon oil from room temperature to 150 °C due to the formation of a drainage surface structure and its temperature insensitivity. Adhesion operation under‐water/oil over a wide temperature range is achieved via a hydrophobic oil‐draining structure and temperature‐insensitive loss factor. A key point is to use methoxyethyl and thiourea groups that form hydrophobic and weak hydrogen‐bonding interactions, bringing tan δ close to 1. The other key point is to incorporate the Teflon micron particles to form an oil‐draining structure on adhesive surfaces.